Patrocles of Athens and Patrocles of Thurii. (28th November 2018) - Cropp, Martin; Storey, Ian
Abstract: The Patrocles mocked as an unwashed miser in Aristophanes Wealth 83–85 has been wrongly identified as a tragic poet ( TrGF no. 57). This note explains the error and discusses some possible identifications of Aristophanes' Patrocles.